Faktan ja fiktion rajamailla : kaunokirjallisen journalismin poetiikka suomalaisissa aikakauslehdissä - Lassila-Merisalo, Maria (Jyväskylä studies in humanities, ISSN 1459-4323, 2009)
Abstract: On the borderline of fact and fiction : the poetics of literary journalism in Finnish magazines.
Keywords: aikakauslehdet; journalismi; narratologia; kerronta; fiktio; kaunokirjallisuus; tekstianalyysi; literary journalism; magazine; nonfiction; poetics